“Mermaids” Theme in A. P. Chekhov’s Short Stories «Trouble» and “Nervous Breakdown” (Proceedings of Southern Federal University. Philology, 2020)
Short stories «Trouble» and «Nervous Breakdown» have social and psychological issues. However, as it often happens in A.P. Chekhov’s works, it is realized with the involvement of a folk culture language with which it creates the basis for its national identity. A folklore image of a mermaid and concepts related to it have an important role in these realistic short stories. The image, being constructive in both cases, appears in different forms and performs different functions. In the first case, the mermaid creates an associated field of indifference, devastation. In the second – temptation, fall, seduction.Key words: Chekhov, folk culture, mermaid, «Trouble», «Nervous Breakdown».DOI 10.18522/1995-0640-2020-2-12-17